2018
DOI: 10.1002/cncr.31518
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for locoregional disease recurrence after breast‐conserving therapy in patients with breast cancer treated with neoadjuvant chemotherapy: An international collaboration and individual patient meta‐analysis

Abstract: BCT after NCT appears to be an oncologically safe procedure for a large percentage of patients with breast cancer. Two easy-to-use clinical scores were developed that can help clinicians to identify patients at higher risk of LR and LRR after NCT and BCT and individualize the postoperative treatment plan and follow-up. Cancer 2018;124:2923-30. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 33 publications
1
17
1
4
Order By: Relevance
“…The reason for the excellent outcome is related to the introduction in routine clinical practice of highly effective treatments in specific subtypes of breast cancer, in particular anti‐HER2 agents. Five‐year LRR rates in our study were similar to other reported cohorts 8,30 …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The reason for the excellent outcome is related to the introduction in routine clinical practice of highly effective treatments in specific subtypes of breast cancer, in particular anti‐HER2 agents. Five‐year LRR rates in our study were similar to other reported cohorts 8,30 …”
Section: Discussionsupporting
confidence: 91%
“…Five-year LRR rates in our study were similar to other reported cohorts. 8,30 5 | CONCLUSION Additional step forward towards optimal selection of patients who will benefit from de-escalating in locoregional treatments after NAT is ongoing. It will impact on reducing morbidity while achieving equal or better long-term outcomes, and reflects the real multidisciplinary breast cancer care at the Institutional level.…”
Section: Locoregional Recurrence and Survival Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…While subtype was not analysed in that trial, other significant independent predictors were age and clinical node status. The effect different subtypes have on recurrence rates in patients treated with NAC has been demonstrated by several other studies [26][27][28][29][30][31], where the HR-negative/HER2-positive and triple negative subtypes are associated with increased recurrence rates.…”
Section: Discussionmentioning
confidence: 67%